DC-AC power inverter controlled analogically with zero hysteresis - Fredy E. Hoyos Velasco; Carlos I. Hoyos Velasco; John E. Candelo-Becerra (International Journal of Electrical and Computer Engineering (IJECE), 2019)
This paper presents the design and experimental validation of a DC-AC power inverter, controlled analogically with zero hysteresis. A control circuit was built using analog electronics components, and optocoupler devices are used to couple the control module with the power stage. The design of DC-AC inverter with electronics circuit and implementation are shown in detail.  Experimental results show the effectiveness of control technique and implementation, leading to a robust system concerning load disturbances. The developed inverter offers the possibility of generating regulated output voltages of different signal types, both DC and AC, variable in frequency and in amplitude, useful for feeding a load with various AC signals.